2018
DOI: 10.1073/pnas.1800521115
|View full text |Cite
|
Sign up to set email alerts
|

Efficient compression in color naming and its evolution

Abstract: We derive a principled information-theoretic account of cross-language semantic variation. Specifically, we argue that languages efficiently compress ideas into words by optimizing the information bottleneck (IB) trade-off between the complexity and accuracy of the lexicon. We test this proposal in the domain of color naming and show that () color-naming systems across languages achieve near-optimal compression; () small changes in a single trade-off parameter account to a large extent for observed cross-langu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
260
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 156 publications
(272 citation statements)
references
References 26 publications
11
260
1
Order By: Relevance
“…Rate distortion theory holds promise as a vehicle for general principles because it unifies two frameworks (information theory and statistical decision theory) that already by themselves have broad explanatory reach. Rate distortion theory has been successfully applied to many different cognitive phenomena, ranging from working memory (Sims et al, 2012;Sims, 2016) and absolute identification (Sims, 2018) to language (Zaslavsky et al, 2018) and motor control (Schach et al, 2018). A complete theory in these domains will eventually use mechanistic models to constrain the rate distortion analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Rate distortion theory holds promise as a vehicle for general principles because it unifies two frameworks (information theory and statistical decision theory) that already by themselves have broad explanatory reach. Rate distortion theory has been successfully applied to many different cognitive phenomena, ranging from working memory (Sims et al, 2012;Sims, 2016) and absolute identification (Sims, 2018) to language (Zaslavsky et al, 2018) and motor control (Schach et al, 2018). A complete theory in these domains will eventually use mechanistic models to constrain the rate distortion analysis.…”
Section: Discussionmentioning
confidence: 99%
“…in CIELAB color space, in which the Euclidean distance between nearby colors corresponds roughly to their perceptual dissimilarity (Brainard, ; but see also Komarova & Jameson, ). This visualization shows that there exist potentially relevant perceptual asymmetries of color—and in fact this perceptual structure has been used to explain patterns of color naming across languages (Jameson & D’Andrade, ; Regier et al., ; Zaslavsky et al., ). We wished to understand whether the structure of perceptual color space could also explain the asymmetry in precision documented by Gibson et al., or that in need, or both—a possibility acknowledged by Gibson et al.…”
Section: The Role Of Perceptual Structurementioning
confidence: 97%
“…In each case, following Zaslavsky et al. (), we evaluated the CAP plfalse(cfalse) for each language l (real or artificial) with respect to its color naming distribution plfalse(wfalse|cfalse), and averaged together these language‐specific priors in order to infer a universal need distribution . That is, we defined pfalse(cfalse)=1Lfalse∑l=1Lplfalse(cfalse),where L = 111 is the number of languages in the WCS+ dataset.…”
Section: Inferring Need From Naming Datamentioning
confidence: 99%
See 1 more Smart Citation
“…. It has been suggested that similarities of color categorization across cultures is optimized to communicate efficiently about the irregularly shaped perceptual color space (Abbott, Griffiths, & Regier, 2016;Zaslavsky, Kemp, Regier, & Tishby, 2018;Zaslavsky, Kemp, Tishby, & Regier, 2019). Evidence for this idea is based on the irregular distribution of maximally saturated Munsell chips and naming data from the World Color Survey (WCS).…”
Section: Perceptual Salience Of Focal Colorsmentioning
confidence: 99%